An Exploration of the Subtypes of Male Youth Adjudicated for Sex Offenses: A Latent Class Analysis Based on Personal, Offense, and Victim Characteristics - Büker, Hasan; Cohen, Achraf; ERBAY, AYHAN (Sage Publications Inc., 2022)
This study intended to explore possible variations among youth adjudicated for sexual offenses based on personal criminogenic factors, offense, and victim characteristics. Utilizing a data set collected from the juvenile court files in Turkey (n = 460), the Latent Class Analysis revealed that the study sample included three different subgroups with distinct features: "non-delinquent, peer victim-targeting," "non-delinquent, younger victim-targeting," and "delinquent, versatile" youth adjudicated for sex offenses. The first two of these groups were similar in terms of having low levels of delinquency, while the third group included the lowest number of youth with significantly broad delinquent activity patterns. These findings were in line with the results of previous studies, and the implications were discussed for future research and policy development.
Keywords: Youth; Juvenile; Sex Offense